2018
DOI: 10.1177/1833358318794501
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic medical record templates improves quality of care for patients with infantile spasms

Abstract: The use of protocolised EMRTs may improve the quality of patient care in IS and other rare diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…For two NCP steps: Nutrition Intervention, and Nutrition Monitoring and Evaluation, this was confirmed through an association between the existence of pre-set EHR pre-defined headings and the implementation level of standardised NCPT terms. Structured templates in the EHR have been shown to improve quality of both the clinical documentation and the care given (Santoro et al, 2021; Vetter and Kim, 2021). The design of intuitive data entry interfaces, such as autocomplete functions, abbreviation and acronym expansion (Lee et al, 2013), or check boxes and drop-down lists (Bennett and Steen, 2010), have been suggested as important implementation strategies for the SNOMED CT terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For two NCP steps: Nutrition Intervention, and Nutrition Monitoring and Evaluation, this was confirmed through an association between the existence of pre-set EHR pre-defined headings and the implementation level of standardised NCPT terms. Structured templates in the EHR have been shown to improve quality of both the clinical documentation and the care given (Santoro et al, 2021; Vetter and Kim, 2021). The design of intuitive data entry interfaces, such as autocomplete functions, abbreviation and acronym expansion (Lee et al, 2013), or check boxes and drop-down lists (Bennett and Steen, 2010), have been suggested as important implementation strategies for the SNOMED CT terms.…”
Section: Discussionmentioning
confidence: 99%
“…Facilitation includes the role of a person, either external or internal, supporting the implementation of changes in practice (Harvey and Kitson, 2016). Technological aspects such as compatibility with existing terminologies or EHR systems have been highlighted as key to implementation of standards in healthcare documentation (Vetter and Kim, 2021;Lee et al, 2013;Bennett and Steen, 2010;Santoro et al, 2021;Fennelly et al, 2021;Højen et al, 2014;Liu et al, 2010). Further, access to the EHR has been pointed out as a possible enabler for NCPT implementation among dietitians, both in an Australian study from 2013 and in a global survey from 2020 (O'Sullivan, 2013;Lövestam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bremond-Gignac et al showed the benefit of an ophthalmology-specific EMR for collecting a comprehensive ocular visual phenotype useful for clinical research 18 . Other approaches consisted in adding disease oriented predefined templates to existing EHRs, for example "infantile spasms template" 19 . On the other hand, a horizontal approach would consist in finding a way to explore all the diseases, including rare diseases, in a common format.…”
Section: Structured Ehrs For Translational Researchmentioning
confidence: 99%
“…Given the ubiquity and ease of developing templated notes to facilitate documentation within the EHR among practicing clinicians, residents, and students in many countries, creation of a templated note guiding students through the H&P 360 domains could be one approach to promote uptake. EHR-based template studies to date have focused on inpatient resident and faculty subjects with primary endpoints including note quality, quality of care, and time to note completion [12][13][14]. However, few studies have evaluated the use of templates to intentionally improve documentation related to patient perspectives and social and behavioral determinants of health [15,16]; most such initiatives have centered on interprofessional team members rather than on promoting psychosocial documentation within a physician's scope of work [17,18].…”
Section: Introductionmentioning
confidence: 99%